2020
DOI: 10.1155/2020/8860466
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Physical Performance and Working Mechanism of Asphalt Containing a Surfactant Warm Mix Additive

Abstract: This paper analyzes the influence of a surfactant warm mix additive on unmodified asphalt’s conventional performance, viscosity-temperature characteristics, surface energy, and spreading performance on aggregate surfaces. The effect of the additive on asphalt’s microstructure was explored by infrared (IR) spectral analysis. The results show the additive has little influence on the penetration, softening point, ductility, and viscosity-temperature characteristics of asphalt; this suggests that the additive does… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…Typical among those is the surfactant WMA, which is widely used in road engineering. Shi et al [14] systematically studied the mechanism of the surfactant WMA. The results showed that the additive mainly improved the warm mix effect by providing a lubrication effect at the asphalt-aggregate interface rather than directly reducing the viscosity of asphalt.…”
Section: Introductionmentioning
confidence: 99%
“…Typical among those is the surfactant WMA, which is widely used in road engineering. Shi et al [14] systematically studied the mechanism of the surfactant WMA. The results showed that the additive mainly improved the warm mix effect by providing a lubrication effect at the asphalt-aggregate interface rather than directly reducing the viscosity of asphalt.…”
Section: Introductionmentioning
confidence: 99%
“…WMA technology originated in Europe [9], and has been widely used all over the world [10]. The purpose of WMA technology is to reduce the viscosity of asphalt binder at high temperature [11,12] by various methods such as the use of organic viscosity reduction additives [13], the foaming viscosity reduction method [14] or using surface-active viscosity reduction additives [15] without reducing the construction quality and mixture performance of the resulting asphalt mixtures, so as to reduce the mixing temperature of these mixtures [8,16]. Compared with HMA, WMA can reduce fuel consumption by more than 40% and reduce the asphalt aging effects caused by high temperatures [17].…”
Section: Introductionmentioning
confidence: 99%
“…Warm mix asphalt (WMA) refers to a form of asphalt mixture with mixing and compaction temperatures 20-55 • C lower than typical hot mix asphalt (HMA) [1][2][3]. The goal of WMA is to produce mixtures with substantially the same road performance and construction workability as HMA under significantly reduced production temperatures [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…However, thus far, the mechanism by which WMA technology makes the mixture easy to mix and compacted at low temperatures is not fully understood [18]. It was found that the reduction in binder viscosity caused by WMA additives was insufficient to explain the decrease in the production and compaction temperature of the final mixture in the field [2,19,20]. Conversely, in some cases, the addition of WMA additives strengthens the viscosity of the binder [18].…”
Section: Introductionmentioning
confidence: 99%